Psychological disorders and personality characteristics of with gastro-esophageal reflux disease - Manzoor, Asma; Ajinkya, Shaunak A.; Jadhav, Pradeep R.; Ghildiyal, Rakesh P. (International Journal of Research in Medical Sciences, 2017)
Background: Gastro-esophageal reflux disease (GERD) can be traced back to disorders of the gastro-esophageal junction but several psychological factors interact to affect treatment outcomes. There is sparse literature from India regarding psychological co-morbidity and personality characteristics in patients with GERD. Aim and Objectives: To study the co-morbid psychological disorders and personality profiles in patients suffering from GERD. Methods: Two hundred patients with GERD-related symptoms were randomly screened for psychological disorders and personality characteristics using 30-item General Health Questionnaire (GHQ) and Sixteen Personality Factor Questionnaire (16PF) respectively. Patients who screened positive for presence of co-morbid psychological disorders were further interviewed using Structured Clinical Interview for DSM-IV Axis 1 Disorders (SCID-1) to find out the type of psychological disorder. Results:The prevalenceofpsychological co-morbidity in patients with GERD-related symptoms in our sample was foundto be 40%. Major depressive disorder was the most common psychological disorder found co-morbid in these patients. Alcohol dependence was significantly observed in males; while in females, major depressive disorder and generalized anxiety disorder was more commonly seen. Regarding personality characteristics, a higher degree of neuroticism and risk-taking attitudes was found in patients of GERD with associated psychological co-morbidity Conclusions:This study suggests that the management of GERD may include psychological evaluations and possibly interventions in standard treatment protocols.